The Regulatory Approval Process for Generic Products in African Continent - Ridah Shaista Shanavas; Sheik Zakir Hussain; Niveditha Yarlagadda; Erukulla Sreedhar; Tatipalli Madhukar Reddy; Akula Kalyan Chakravarthy (International Journal of Pharma and Bio Sciences, 2022)
A quality regulatory system is a critical tool in protecting public health against the unauthorized flow and use of medical products in any country. This review summarizes the current status of National Medicines Regulatory Authorities (NMRAs) in Africa and various requirements that have been established to evaluate the registration procedures in the continent. The regulatory strategy during the product development is essential before the commencement of developmental work in order to avoid major surprises after the submission of the application. The quality, safety, and efficacy of all medicines in the respective country are regulated by the regulatory authorities. All countries in Africa (except the Sahrawi Republic), have NMRAs but their organizational setup and functionality vary. Some are located within Ministries of Health while others are semi-autonomous. With 70% to 90% of the drugs in the African continent still following the import route, strengthening the regulatory framework has been a key focus area. The African Vaccines Regulatory Forum, African Medicines Regulatory Harmonization Initiative, Network of Official Medicines Control Laboratories, and WHO Prequalification Scheme have helped countries strengthen their regulatory capacities over the years. Accordingly, there is progressive improvement in a regulatory capacity, particularly in quality control and post-marketing surveillance, pharmacovigilance, and clinical trials oversight. However, with changing dynamics of the health conditions wherein Africa is struggling with both infectious diseases and non-communicable chronic diseases, multinational pharmaceutical companies are targeting to accelerate access to medicines, approved globally, to Africa. The paper here aims to guide international pharmaceutical companies who would like to leverage approval in other markets for faster approvals in the African continent.